PENERAPAN MEDIA AUDIO VISUAL DALAM UPAYA MENINGKATKAN PEMAHAMAN SISWA KELAS VIII PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTs SA AL-MUSTAWA RANDUBLATUNG KABUPATEN BLORA - Nurkayati, Siti; Rizki, Citra Hijriyati (Jurnal Studi Islam dan Sosial, 2023)
A Effective learning is learning that is able to condition students to have motivation and understand the material presented. One of the obligations of educators to fulfill these obligations is by utilizing learning media in teaching and learning activities, including the media in question is audio visual media. This study aims to (1) find out how the application of audio-visual media in an effort to increase the understanding of class VIII students at MTs SA Al -Mustawa Randublatung Blora. (2) To find out the supporting factors and inhibiting factors for the application of audio-visual media in an effort to increase the understanding of class VIII students in the subject of Islamic Cultural History (SKI) at MTs SA Al -Mustawa Randublatung Blora. (3) To find out the results of the application of audio-visual media in an effort to increase the understanding of class VIII students at MTs SA Al-Mustawa Randublatung Blora. The research method used is a qualitative method with the type of field research (Field Research). With the nature of qualitative descriptive research. Data collection is done by way of interviews, observation and documentation. Data analysis techniques include data reduction, data presentation, conclusions and verification. The results of the study are as follows: (1) The form of application of audiovisual media goes through several stages, namely preparation, implementation and follow-up. Film/video media that are applied in learning are adjusted to learning objectives, and the teacher communicates the activities to be carried out with students, and there is follow-up from the teacher as material reinforcement. (2) The supporting factor for the application of audiovisual media is the availability of adequate facilities and infrastructure. While the inhibiting factors are differences in the level of intelligence of students and frequent power outages. (3) The results of the application of audio-visual media in an effort to increase class VIII students' understanding of Islamic Cultural History (SKI) subjects show that students are able to understand the content of the material presented.